HUBUNGAN KEMAMPUAN AWAL MATEMATIKA DENGAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII SMP 12 TARAKAN - Ferryansyah Ferryansyah; Azwar Anwar (Mathematics Education And Application Journal (META), 2020)
AbstractThe purpose of this study was to determine the relationship between the ability of early mathematics with the ability to understand mathematical concepts of eighth grade students of SMP Negeri 12 Tarakan. This type of research uses ex post facto research. The population in this study were all students of class VIII of SMP Negeri 12 Tarakan and research samples of students of class VIII-4 by using simple random sampling. Data collection techniques using instrument the ability of early mathematics test and the ability to understand mathematical concepts test with using Pearson Correlation test data analysis. Based on the analysis results obtained by the correlation coefficient values obtained by 0.674 and the value of r = 1. So that the relationship between the two variables is a strong relationship with a positive direction. The significance value of 0,000 0.05 which means rejecting H0 and accepting H1. Thay way there is a relationship between the ability of early mathematics with the ability to understand mathematical concepts of eighth grade students of SMP Negeri 12 Tarakan.Keywords: Ability of Early Mathematics, Ability to Understand Mathematical ConceptsAbstrakTujuan penelitian ini adalah untuk mengetahuihubungan kemampuan awal matematika dengan kemampuan pemahaman konsep matematika siswa kelas VIII SMP Negeri 12 Tarakan. Jenis penelitian menggunakan penelitian expost facto.Populasi pada penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 12 Tarakan dan sampel penelitian siswa kelas VIII-4 dengan menggunakan simple random sampling. Teknik pengumpulan data menggunakan instrumen tes kemampuan awal matematika dan tes kemampuan pemahaman konsep matematika dengan menggunakan analisis data uji Korelasi Pearson.Beradasarkan hasil analisis diperoleh nilai nilai koefisien korelasi sebesar 0,674 dan nilai r = 1. Sehingga hubungan kedua variabel merupakan hubungan kuat dengan arah positif. Adapun nilai signifikansi sebesar 0,000 0,05 yang berari tolak H0 dan terima H1. Dengan demikian ada hubungan kemampuan awal matematika dengan kemampuan pemahaman konsep matematika siswa kelas VIII SMP Negeri 12 Tarakan.Kata kunci: Kemampuan Awal Matematika, Kemampuan Pemahaman Konsep Matematika